KELAYAKAN OPERASIONAL SEKOLAH SWASTA BERBASIS DANA BOS (BANTUAN OPERASIONAL SEKOLAH) TANPA SPP (SUMBANGAN PEMBINAAN PENDIDIKAN) - Zakiati, Dyah; Ahmad, Masduki; Rochimah, Heni (STKIP Pesisir Selatan, 2025)
Private schools play a crucial role in the provision of primary and secondary education in Indonesia, particularly in areas not yet fully covered by public education services. This study aims to analyze the operational feasibility of a private junior high school (SMP) operating under the Regular School Operational Assistance (BOS) fund without tuition fees. Using a descriptive quantitative approach, an operational budget simulation was conducted, taking into account the minimum requirement standards and the commonly used teacher-student ratio assumptions. Based on the 2025 BOS unit cost of Rp1,260,000 per student, the simulation results indicate that a private school requires at least 507 students (with a teacher-student ratio of 1:25) to 583 students (with a ratio of 1:20) to cover all routine operational needs without relying on other funding sources. These findings confirm that only large-scale private schools can likely survive without tuition fees, even with high management efficiency and a lean organizational structure. Conversely, small schools scattered across Indonesia face the risk of becoming unsustainable without additional funding alternatives or policy interventions. Therefore, this study recommends an affirmative policy in the form of adjusting the BOS unit costs based on the number of students, region, and institutional status, to ensure the sustainability of equitable and fair education.